Supply chain integration, landside operations and port accessibility in metropolitan Chicago. (February 2016) - Clott, Christopher; Hartman, Bruce C.
Abstract: Seaports have traditionally been the focus of maritime logistics supply chains. Changing production patterns demanding greater end to end visibility by customers and accessibility to key inland population centers assume greater importance in the organization and design of transport resources and cargo flows. While synchronization of all aspects of the supply chain has become an operational necessity for firms, it is often held hostage to the efficiency of hinterland networks who must respond to a large group of stakeholders with sporadic coordination. This is particularly true when looking at the central US city and region of Chicago, a critical intermodal exchange point for truck, air and river barge traffic domestic and global, as well as a major central distribution location. This paper analyzes supply chain integration (SCI) efforts in the metropolitan Chicago region and considers efforts by public and private actors to collaborate for region-wide SCI improvements. Pareto analysis suggests that concentrated freight corridors exist, influencing freight planning for regional transportation networks more directly than diffused regional freight movements. If the corridor service becomes less responsive or congested the corridor will move to different end nodes within the broad region. Regional planning must thus address national, regional, and local moves. Private/public sector infrastructure firms should address functional cooperation on SCI by focusing on corridors as well as local improvements. Highlights: We discuss Chicago's freight bottleneck and implications for supply chain integration (SCI). We analyze drivers of SCI in intermodal transport, and cases of Chicago infrastructure activity. A Pareto analysis finds the key Chicago freight supply chain corridors. Cases show that public/private infrastructure projects have difficulty addressing SCI challenges. Deep inter-regional corridor functional cooperation on SCI is the key for success.